BIODIESEL PRODUCTION FROM WASTE COOKING OIL AND ISOPROPANOL FLUID BY USING TRANSESTERIFICATION TECHNOLOGY AND OPTIMIZING THE PROCESS BY USING RESPONSE SURFACE METHOD (RSM) - SHUNAIA , AHMED A.; JAZIE, ALI A. (Journal of Duhok University, 2023)
Biodiesel represents an important future source of renewable energy, and it consists of waste cooking oil. Waste cooking oil is fatty acid that needs transesterification to produce a methyl or ethyl ester. This research is a study of biodiesel production from two sources, isopropanol and waste cooking oil by using a process of transesterification. The temperature during the experiment was between 300 and 350 °C, the co-solvent(hexane) was between 0 and 8 ml, and the ratio of oil to isopropanol molar ratio was between 4 and 12. According to the findings of optimization studies. The supercritical isopropanol reaction can produce an ideal yield of 91.625% under optimal conditions (the molar ratio of isopropanol to oil is 8.413, the temperature is 326.762 °C, and the solvent is 4.984 ml). The technique was optimized by looking at the biodiesel yields from waste cooking oil and isopropanol under various circumstances. The parameters of the process for the transesterification reaction were optimized using response surface methodology (RSM). The models were effective in explaining the response of the variations regard the three investigated factors. The fuels quality of the produced biodiesel was compared to those required by ASTM for biodiesel.